Analysis of the Effect of Working Environments, Organizational Citizenship Behavior (OCB), and Work Diciplines on Employees Performances at the Lestari Kertosono Sugar Factory - Noviana, Sela; Muslih, Basthoumi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This current study aimed to analyze the impact of work environment, organizational citizenship behavior (OCB), and work disciplined on employees' performances at Lestari Kertosono Sugar Factory. Design/Methode/Approach : This study uses a descriptive research approach with quantitative analysis techniques. The sampling technique uses total sampling, namely all employees totaling 45 people. Data collection techniques were made through observation, interviews and a questionnaire. The technique used for analyzing these data is a multiple linier regresi analyzer. Research Finding : Working Environmental, Organizational Citizenship Behavior and Work Discipline partially and simultaneously affect Employees Performances. To increase employees' performances, the management of Lestari Kertosono Sugar Factory is advised to create a better work environment by paying attention to aspects of comfort and facilities, encouraging OCB behavior through reward and recognition programs, and improving work discipline by setting clear standards and providing the necessary training. By implementing this strategy, employee performance is expected to improve, which in turn will support the growth of the corporate success and the enterprise's competitiveness in the market. Theoretical contribution/Originality : This theoretical contribution is to provide new insights into the influence of working environments, OCB, and employee disciplinary to employee performance, as well as add to the existing literature on this topic. Practitionel/Policy implication : This experiment is supposed to be able to provide strategic recommendations for company management in designing strategies that can improve employee performance through improving influencing factors, such as work environment, organizational behavior, and work discipline. Research limitation : This study has several limitations. First, the sample size includes only 45 employees, making it less representative for the sugar industry population. Second, the cross-sectional nature of this study only provides an overview at one time without capturing long-term dynamics. Third, external factors such as economic conditions or company policies that may affect performance were not measured. Finally, the research focus was limited to work environment, OCB, and work discipline, without considering other variables such as motivation or job satisfaction.